HOST PLANTS OF THE CITRUS FLATID PLANTHOPPER IN THE ARBORETUM NAMED AFTER B. F. OSTAPENKO (UKRAINE) - Васильєва, Юлія; Леженіна, Ірина (SWorldJournal, 2025)
The article is devoted to the study of host plants of the invasive phytophage Metcalfa pruinosa (Say, 1830), within the territory of the arboretum named after B.F. Ostapenko. The Citrus Flatid Planthopper is a dangerous adventive species that actively exp